THE EFFECT OF LEADERSHIP AND SUPERVISOR SUPPORT ON JOB SATISFACTION IN BNI KCU MANADO OFFICE - Harimu, Friska P.M.; Tumewu, Ferdinand (FEB Universitas Sam Ratulangi Manado, 2016)
A decisive leadership of an organization or company reaches the point of success, therefore this research is important to know how to effect the leadership and supervisor support on job satisfaction in BNI KCU Manado Office. Because after the leadership, an important role is the employees in a company to achieve the profits or success. Therefore, it is necessary to know what the strategy made by leaders and supervisors who make every employee feel satisfied in doing work in BNI KCU Manado Office. The strategy that applied by leadership and supervisor support in BNI KCU Manado Office is to provide motivation to work, rewards and create a sense of family in the world of work. Things like, that make every employee feel comfortable and satisfied in employment. This study uses quantitative methods associated with multiple regression analysis. Respondents are employees of BNI KCU Manado Office. The study concluded that there is a significant influence of leadership and supervisor support on employee job satisfaction simultaneously and partially. Researcher suggest for leadership and supervisor support in BNI KCU Manado Office, remain consistent with existing strategies to direct and guide each employee so well that gets quality work of employees who are satisfied with the existing leadership. Keywords: leadership, supevisor support, job satisfaction